Improving the impact of menstrual health innovations in low- and middle-income countries: a theory of change and measurement framework - Marni Sommer; Garazi Zulaika; Margaret L Schmitt; Samantha Khandakji; Kristin Neudorf; Leeat Gellis; Penelope A Phillips-Howard (Journal of Global Health Reports)
There exists growing global attention focused on tackling the menstrual management related challenges facing adolescent girls and women in low- and middle-income countries (LMIC). This includes a surge of growth in new and locally produced menstrual products, often accompanied by innovative distribution approaches aimed at enhancing accessibility, along with the provision of menstruation-related education. Increasing global investments support the development of such products by local and international menstrual innovators, with the aim of shifting from product development towards achieving scale. Parallel to such efforts, there is a need for rigorous monitoring to evaluate the process and impact of implementation, to ensure resources are effectively utilized. In response, a new measurement model was developed that includes a Theory of Change (ToC) and measurement framework, to enable improved measurement of the impact and growth of menstrual product innovations. These tools aim to help investors to more effectively monitor and assess the impact of investments. They will also support social entrepreneurs, innovators, and non-governmental organizations to adopt approaches that are most effective for impacting the lives of menstruating adolescent girls and women across LMIC. This paper seeks to introduce the ToC and monitoring and evaluation framework as supportive resources that provide a common framework for the global community to utilize as both investors and social entrepreneurs seek to develop more scalable menstrual solutions globally.